2016
DOI: 10.14719/pst.2016.3.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of Pteridophytes from Satara District, Maharashtra (India)

Abstract: The diversity and distribution along different ecological gradients of eighty six species of pteridophytes from the Satara district were studied. Amongst these species most common species were viz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Also, species richness and abundance of pteridophytes are greater in shady forests than in more open ones or in open vegetation types because there are more shade tolerant species (umbrophiles) of pteridophytes than pioneers/ heliophiles (Tryon & Tryon 1982, Della 2016). Chen et al (2014), Daly et al (2006), Das et al (2013), Della (2016), Dzwonko & Kornas (1994), Eisner & Peterson (1998), Gamarra et al (2003), Gehrig-Downie et al (2012), Goebel et al (2006), Goforth (2006), Granville (1984), Guarino et al (2012), Guimarães et al (2014), Halme & Bodmer (2007), Haq et al (2017), Hemp (2002), Hernández et al (2013), Higgins et al (2011), Johns (1985, Karst et al (2005), Kessler (2001), Kessler & Bach (1999), Khwaiphan & Boonkerd (2008), Klinka et al (1989), Loschi et al (2010), Medeanic et al (2016), Nettesheim et al (2014), Nóbrega et al (2011), Norton (1994, Page (2002), Patil et al (2016), Pos & Sleegers (2010), Ranieri (2015), Richard et al (2000), Richardson & Walker (2010), Rocha-Uriartt et al (2016), Ruokolaine...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, species richness and abundance of pteridophytes are greater in shady forests than in more open ones or in open vegetation types because there are more shade tolerant species (umbrophiles) of pteridophytes than pioneers/ heliophiles (Tryon & Tryon 1982, Della 2016). Chen et al (2014), Daly et al (2006), Das et al (2013), Della (2016), Dzwonko & Kornas (1994), Eisner & Peterson (1998), Gamarra et al (2003), Gehrig-Downie et al (2012), Goebel et al (2006), Goforth (2006), Granville (1984), Guarino et al (2012), Guimarães et al (2014), Halme & Bodmer (2007), Haq et al (2017), Hemp (2002), Hernández et al (2013), Higgins et al (2011), Johns (1985, Karst et al (2005), Kessler (2001), Kessler & Bach (1999), Khwaiphan & Boonkerd (2008), Klinka et al (1989), Loschi et al (2010), Medeanic et al (2016), Nettesheim et al (2014), Nóbrega et al (2011), Norton (1994, Page (2002), Patil et al (2016), Pos & Sleegers (2010), Ranieri (2015), Richard et al (2000), Richardson & Walker (2010), Rocha-Uriartt et al (2016), Ruokolaine...…”
Section: Methodsmentioning
confidence: 99%
“…Although lycophytes and ferns reach high frequency and abundance in humid forests, they also occur in dry environments, where some genera can be quite species-rich (Moran 2008). Locally pteridophytes are not randomly distributed, as their presence or absence reflects microhabitat characteristics, such as soil texture and fertility, atmospheric temperature and humidity, precipitation, and light intensity (Nóbrega et al 2011, Patil et al 2016. Hence the distribution of pteridophytes being strongly related with abiotic variables, this group presents a great potential as EI.…”
Section: Introductionmentioning
confidence: 99%
“…Gleicheniaceae, Davalliaceae, Blechnaceae, and Athyriaceae in the study area is represented by a single species only (Fig. 2) Each fern species has its micro habitat requirements, which vary based on various factors such as temperature, humidity, soil type, soil pH, light intensity, and other factors, and are often quite specific in their requirements with narrow ecological amplitude [4]. In the present study, the majority of the species were found in terrestrial or plant substrates that retain maximum moisture content throughout the year.…”
Section: Species Richnessmentioning
confidence: 99%
“…Pteridophytes are considered to be important because of their evolutionary significance. They are a notable ancient group of species with a significant number of relict and endemic ones [4]. Pteridophytes are considered as an intermediate between the higher vascular plants (gymnosperms and angiosperms) and lower nonvascular plants because of their specialized vascular system.…”
Section: Introductionmentioning
confidence: 99%
“…Due to diversified topography, variable climatic conditions and geographical position, about 1200 species of pteridophytes are reported from India (Dixit, 1984(Dixit, , 2000Sukumaran et al, 2009;Dudani et al, 2011;Dongare, 2013, Kavitha et al, 2015;Kachhiyapatel et al, 2015;Patel et al. 2015;Patil et al, 2012Patil et al, , 2014Patil et al, , 2016Rajput et al, 2016), in which nearly 17% species are endemic (Sanjappa and Venu, 2010). However, similar studies are lacking on the diversity of the state of Gujarat.…”
Section: Introductionmentioning
confidence: 99%